OLT1177 (Dapansutrile), a Selective NLRP3 Inflammasome Inhibitor, Ameliorates Experimental Autoimmune Encephalomyelitis Pathogenesis - Sánchez-Fernández, Alba; Skouras, Damaris B.; Dinarello, Charles A.; López-Vales, Rubèn (Frontiers in Immunology, 2019)
IL-1β and IL-18 are pro-inflammatory cytokines that are linked to inflammation. Activation of the NOD-like receptor protein 3 (NLRP3) inflammasome is required for the maturation and secretion of IL-1β and IL-18 and, thus, plays a key role in the pathogenesis of many inflammatory conditions, including multiple sclerosis (MS). OLT1177™ (dapansutrile) is a newly developed drug that is safe in humans and inhibits specifically the NLRP3 inflammasome. In the present study, we investigated whether OLT1177 exerts therapeutic effects in experimental autoimmune encephalomyelitis (EAE), a mouse model of MS. We found that EAE mice fed an OLT1177-enriched diet prophylactically were significantly protected against functional deficits and demyelination in the spinal cord. We also demonstrated that prophylactic oral administration of OLT1177 led to marked reduction (~2-3 fold) in the protein levels of IL-1β and IL-18, as well as, IL-6 and TNFα, in the spinal cord of EAE mice. Moreover, prophylactic oral administration of OLT1177 significantly attenuated the infiltration of CD4 T cells and macrophages in the spinal cord. We also demonstrated that oral administration of OLT1177, starting at disease onset, resulted in significant amelioration of the clinical signs of EAE. Overall, these first data suggest that OLT1177 could have clinical benefit for the treatment of MS in humans.